2016 riparian vegetation within the Colorado River Basin - Evangelista, Paul; Woodward, Brian; West, Amanda; Vorster, Tony; Young, Nicholas; Girma, Rebecca; Hatcher, Emma; Carroll, Sarah; Vashisht, Amandeep; Tilakamonkul, Chanin; Campbell, Emily (Colorado State University. Libraries, 2017)
GeoTiff raster of 2016 riparian vegetation within the Colorado River Basin. This map was created from a random forest model developed in Google Earth Engine.
A raster that depicts modeled riparian vegetation in 2016. Training data were collected in Google Earth Engine using National Agriculture Imagery Program (NAIP) imagery. Presence and absence riparian vegetation locations were ocularly estimated within Environmental Protection Agency (EPA) ecoregion III boundaries within the Colorado River Basin. Random forests models were then developed at each ecoregion using Landsat composites and associated vegetation indices. Results were mosaicked to create a continuous raster across the Colorado River Basin.
Users of these maps and other analysis products are solely responsible for interpretations made from these products. The Natural Resource Ecology Laboratory makes every effort to ensure this map is free of errors but does not warrant the map or its features are either spatially or temporally accurate or fit for a particular use. The Natural Resource Ecology Laboratory provides this map without any warranty, either express or implied.
Natural Resource Ecology Laboratory (NREL)
Keywords: riparian vegetation; random forest; Google Earth Engine; Landsat